Colonial Natchitoches : a Creole community on the Louisiana-Texas frontier - Burton, H. Sophie, 1966- (Elma Dill Russell Spencer series in the West and Southwest ;, 2008)
Strategically located at the western edge of the Atlantic World, the French post of Natchitoches thrived during the eighteenth century as a trade hub between the well-supplied settlers and the isolated Spaniards and Indians of Texas. Its critical economic and diplomatic role made it the most important community on the Louisiana-Texas frontier during the colonial era. Despite the community's critical role under French and then Spanish rule, Colonial Natchitoches is the first thorough study of its society and economy. Founded in 1714, four years before New Orleans, Natchitoches developed a cr.